INTEGRATION OF REPRODUCTIVE HEALTH SERVICES INTO HIV PREVENTION FOR WOMEN OF REPRODUCTIVE AGE: A SYSTEMATIC LITERATURE REVIEW - Febri Adriati; Herliana (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Women of reproductive age contribute a significant proportion of HIV cases both in Indonesia and globally, yet early detection coverage and progress toward the 95-95-95 targets remain below national goals. Reproductive health services such as family planning (FP) and antenatal care (ANC) represent strategic contact points that could be integrated with HIV prevention services, though evidence on the forms and effectiveness of such integration, particularly in the Indonesian context, remains under-synthesized. To identify, appraise, and synthesize scientific evidence on the integration of reproductive health services into HIV prevention efforts among women of reproductive age.This systematic literature review followed PRISMA 2020 guidelines, searching PubMed, Scopus, ScienceDirect, Google Scholar, Garuda, and SINTA for articles published 2015–2025. Study selection used the PICOS framework, followed by quality appraisal using the JBI Critical Appraisal Checklist and CASP, with narrative synthesis of findings.Nine studies met the inclusion criteria, comprising multi-country systematic reviews and primary studies from Indonesia. Integration of FP services with HIV testing consistently increased early detection coverage (35–99% in integrated services vs. 20–95% in non-integrated services). Comprehensive HIV knowledge among women of reproductive age was associated with interest in VCT, while implementation of Indonesia's PMTCT program at the primary care level continued to face health system barriers and social stigma. Integrating reproductive health and HIV prevention services is a strongly evidence-based strategy for improving early HIV detection among women of reproductive age; however, its success in Indonesia requires strengthening primary health systems, improving health literacy, and simultaneously addressing stigma.